Institutional aspects of the fisheries management among the Sami people living in the Murmansk region - Osokina, Marianna (UiT The Arctic University of Norway, 2019)
This master thesis will consider the institutional aspects of traditional fisheries regulation among the small Indigenous minorities of the North, Siberia and the Far East of Russia, using the Kola Sámi settled in Murmansk region as case. The thesis studies the potential for influence of local institutions on the traditional fisheries management. Based on documents and internet sources the thesis explores how regional authorities in their collaboration with communities and industries implement and adapt the norms and principles of federal and regional legislation relating to the traditional use of natural resources, particularly fisheries. Taking into account the specificities of regional economic, social and ecological conditions as well as cultural and ontological background of the Kola Sámi, to the thesis addresses the effectiveness of underlying institutional set-up for traditional fisheries and how the traditional institutions can be incorporated in existing institutional structure.